TRANSLATION TECHNIQUES, QUALITY, AND DIFFICULTIES IN ENGLISH-INDONESIAN COLLOCATION TRANSLATION - Safriyaldi Rahaldi Hasibuan; Havid Ardi (Indonesian EFL Journal, 2025)
This study aims to identify students’ translation techniques, quality, and difficulties in translating collocation from English into Indonesian at the third semester English education students of Universitas Negeri Padang. The study employed descriptive-qualitative method. The participant of this study is 27 students from class K-5 English Education study program of Universitas Negeri Padang. Translation test and questionnaire were used as the instruments to collect the data. In addition, the collection of data also was assisted by concordance tool “KORTARA” Software. Based on the result, the researcher obtained 10 translation techniques used by the students in translating collocation from the source language into target language from the most frequent to the less frequent were establish equivalent, modulation, amplification, generalization, variation, particularization, reduction, discursive creation, literal translation, and calque. The most frequently translation technique used by the students was establish equivalent. This is because of the word that is recognized as equivalent n the target language. Second, the result from the students’ translation quality from two aspects shows that the total mean score of accuracy was 2.46 and acceptability was 2.49. Based on these aspects of accuracy and acceptability, the total mean score of translation quality in translating collocation was 2.47 and categorized in the moderate translation quality. Last, the result shows that the students’ difficulties in translating collocation consist of 5 difficulties start from the most frequent to the less frequent were the engrossing effect of source text patterning and marked collocations in the source language and categorized very high difficulty. Meanwhile, the less frequent difficulties faced by students in translating collocation were misinterpret the meaning of the collocation into the receptor language, culture-specific collocation, and the tension between accuracy and naturalness and categorize high difficulty.